The usage of instagram and e-commerce platform during covid-19 among mothers / Ahlam Abdul Aziz, Rahayu Mohd Rashid, Wardatul Hayat Adnan - Abdul Aziz, Ahlam; Mohd Rashid, Rahayu; Adnan, Wardatul Hayat (Centre For Media And Information Warfare Studies, 2021)
Instagram made a shift into the e-commerce space. Almost overnight, it has become a popular marketing instrument. The usage of Instagram in the e-commerce platform has been expanding rapidly and is growing tremendously. The purpose of this study is to understand the underlying factors that influence the usage of Instagram as a shopping tool among Mothers in Malaysia during COVID-19. Using the qualitative method and phenomenology approach, the finding reveals several factors that influence Instagram usage, the various purpose of using Instagram, and benefits to the consumers. Twenty samples were selected for this study as to fulfill requirement of the study. The evidence gathered in this study are useful and can be served as guidance for consumer and marketers in using social media in future. Findings revealed that the cost and time efficiency as factors influencing the respondents' online purchase through social media. The consumer can also compare prices conveniently without feeling pressure.